IMPLEMENTASI PENDEKATAN KOOPERATIF DAN KOLABORATIF BERBASIS PEMBELAJARAN MENDALAM UNTUK MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR IPAS SISWA KELAS IV UPTD SD INPRES BAMBAMANURUNG - Eka Nur Imamah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Problems in learning science and science on force in grade IV of UPTD SD Inpres Bambamanurung are characterized by low student activity and learning outcomes completion due to teacher-centered learning and minimal experimental activities. This condition causes students to be less involved in discussions, not confident in expressing opinions, and not yet understand the concept of force in depth. This study aims to implement a cooperative and collaborative approach based on in-depth learning to improve student activity and learning outcomes. The method used is Classroom Action Research (CAR) which is implemented in three cycles through the stages of planning, action implementation, observation, and reflection. The research subjects are 12 students. Actions are carried out through contextual experimental activities, group discussions, presentations, and reflection by combining the principles of individual responsibility and social construction of knowledge. The results of the study showed a significant increase in student activity from 60% in Cycle I to 78% in Cycle II and reaching 95% in Cycle III. The completion of learning outcomes increased from 55% at the initial condition to 90% at the end of the cycle. In addition, there was a change in learning attitudes in the form of increased self-confidence, communication skills, and cooperation. It was concluded that the implementation of a cooperative and collaborative approach based on in-depth learning effectively created more active, meaningful science and science learning and had a real impact on improving the learning outcomes of elementary school students.